Rhythmic trajectories in the hispanic Caribbean: The cases of Arturo, la estrella más brillante, by Reinaldo Arenas, and La guaracha del macho Camacho, by Luis Rafael Sánchez - Díaz Choza, Mateo (2020)
Enjoyment, rhythm and music are constitutive elements of Hispanic Caribbean imagery and identity. The interpretation of two novels from the second half of the 20th century, Arturo, la estrella más brillante (1984) [Arthur, The Brightest Star] by Reinaldo Arenas and La guaracha del Macho Camacho (1976) [Macho Camacho’s Beat] by Luis Rafael Sánchez, shows how this legacy can interact with diverse political and social contexts. For the former, from the experience of sexual dissidence and the repression of the state apparatus of post-revolutionary Cuba, rhythm becomes a vehicle to channel the imagination and seek creative freedom; for the latter, traditional music, mediated by mass culture, allows an explosion of collective enjoyment that energizes Puerto Rican society of the 1970s, marked by stagnation.